1966
DOI: 10.1111/j.1151-2916.1966.tb13304.x
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Phase Transitions in PbZrO3

Abstract: A high‐temperature X‐ray diffraction study of a high‐purity PbZrO3 specimen at 25° to 236°C is reported. The symmetry of the perovskite sub‐cell of PbZrO3 was determined unambiguously by observing the splitting of the line groups N= 12 and N= 16 when the diffraction pattern was indexed on the basis of the perovskite cell being a unit cell for the structure. Diffractometer studies were conducted of the N= 12 line group using Fe Kα radiation and of the N= 16 line group using Cu Kα radiation. The ferroelectric ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(37 citation statements)
references
References 4 publications
3
33
0
1
Order By: Relevance
“…Nevertheless its dielectric [33][34][35][36], piezoelectric [37] and structural [38][39][40] properties as well as the ones with \10% of PbTiO 3 [9] were studied as early as the 50s. The existence of a ferroelectric rhombohedral phase on a narrow range of temperature (503-506 K upon heating and 505-500 K upon cooling) between the paraand antiferroelectric phases was confirmed later [41][42][43] and a detailed study of the phase transitions by combined X-ray diffraction, dielectric and birefringence measurements determined the displacement of lead atoms (described by Kittel's theory of antiferroelectricity [44]) as well as the oxygen octahedra rotation [45]. The possibility to induce a ferroelectric phase thanks to (high) electric fields in the nominally antiferroelectric phase of PbZrO 3 was reported and the electric field-temperature phase diagram for PbZrO 3 established by Fesenko et al [46].…”
Section: Temperature-composition Phase Diagrammentioning
confidence: 77%
“…Nevertheless its dielectric [33][34][35][36], piezoelectric [37] and structural [38][39][40] properties as well as the ones with \10% of PbTiO 3 [9] were studied as early as the 50s. The existence of a ferroelectric rhombohedral phase on a narrow range of temperature (503-506 K upon heating and 505-500 K upon cooling) between the paraand antiferroelectric phases was confirmed later [41][42][43] and a detailed study of the phase transitions by combined X-ray diffraction, dielectric and birefringence measurements determined the displacement of lead atoms (described by Kittel's theory of antiferroelectricity [44]) as well as the oxygen octahedra rotation [45]. The possibility to induce a ferroelectric phase thanks to (high) electric fields in the nominally antiferroelectric phase of PbZrO 3 was reported and the electric field-temperature phase diagram for PbZrO 3 established by Fesenko et al [46].…”
Section: Temperature-composition Phase Diagrammentioning
confidence: 77%
“…The manifestation of the rhombohedral phase in PZO has been reported earlier in single crystals and high-purity ceramics of the material within a narrow range of temperature near T C . [20][21][22][23] In case of thin films, PZO is likely to grow in the cubic phase at the deposition temperature (T d ∼ 575…”
Section: Resultsmentioning
confidence: 99%
“…19 Manifestation of ferroelectricity in high-purity ceramics and single crystals of PZO was also observed in a narrow temperature range near the T C , and in these cases the AFE O to paraelectric-cubic (PE C ) phase transition was found to be associated with an intermediate FE R phase. [20][21][22][23] Room-temperature ferroelectricity in PZO was demonstrated by Ayyub et al 24 for thin films below a critical thickness of ∼500 nm fabricated on p-type Si substrates and was explained in terms of the effective built in electric field at the PZO and Si interface. Various research groups reported that such size-dependent physical properties in different materials are associated with a structural phase transition, which can be achieved by stressing their epitaxial thin films through effective misfit.…”
Section: Introductionmentioning
confidence: 98%
“…The measurements of the length of a specimen at various temperatures of solid materials are usually applied for the determination of the kinetics of phase transformation of PZ Downloaded by [University of Lethbridge] at 20:32 26 June 2016 Table 1 Intensity ratio of 004/240 peak, lattice parameter, unit cell volume, density and transition temperature of PBZ10 ceramics with different amounts of excess PbO [12,13]. The dilatometric thermal expansion of PBZ10 with excess PbO on heating cycle is plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%